The Effect of Hyperbaric Oxygen Therapy to the Amount of Lymphocytes in Oral Candidiasis Immunosuppressed Model - Agni Febrina Pargaputri; Dwi Andriani (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2018)
Background: Oral candidiasis generally caused by Candida albicans with prevalence of 30-50%. C. Albicans proliferation in the oral cavity was canducted by decreasing immune system of the host. Lymphocytes activation in immune system happened when there is a contact between host cell with cell wall of C. albicans as a result of C. albicans antigen. One of therapy to suppress the Candida infection sistemically is by giving hyperbaric oxygen therapy. Purpose: To determine the effects of giving hyperbaric oxygen therapy to the amount of lymphocytes in oral candidiasis immunosuppressed models. Methods: This research was post test only control group design. We used 12 wistar rats which were divided into 3 groups(n=4/3): K-(normal/ healthy wistar rats), K+(oral candidiasis immunosuppressed wistar rats), P1(oral candidiasis immunosuppressed wistar rats which were given hyperbaric oxygen therapy 5 days). K+ and P1 groups were immunosuppressed by giving dexamethasone 0,5mg/day/rat orally for 14 days, added with tetrasiklin 1 mg/day/rat. On the 3rd day immunosuppression, the rats were inducted with C.albicans smeared in the dorsum linguae once every two days for 12 days. Results: The data were analyzed with one way Anova test and showed significant difference among groups (p<0,05). To show the difference between each groups we used LSD test and showed significant difference (p<0,05) between K+ compared with P1, and K+ compared with K-. Conclusion: Hyperbaric oxygen therapy gives effect to the amount of lymphocytes in oral candidiasis immunosuppressed models.